2017
DOI: 10.1007/s13311-017-0542-y
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Effects of Psilocybin

Abstract: Psilocybin and other 5-hydroxytryptamine agonist classic psychedelics have been used for centuries as sacraments within indigenous cultures. In the mid-twentieth century they were a focus within psychiatry as both probes of brain function and experimental therapeutics. By the late 1960s and early 1970s these scientific inquires fell out of favor because classic psychedelics were being used outside of medical research and in association with the emerging counter culture. However, in the twenty-first century, sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
186
0
16

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(206 citation statements)
references
References 55 publications
4
186
0
16
Order By: Relevance
“…Psychoactive tryptamines, particularly psilocybin and psilocin, have recently garnered a great deal of interest because of their potential to treat disorders including anxiety, addiction, and depression (Johnson & Griffiths, 2017;Carhart-Harris & Goodwin, 2017). Of note, psilocybin was recently granted the 'breakthrough therapy' designation by the US Food and Drug Administration (Feltman, 2019).…”
Section: Chemical Contextmentioning
confidence: 99%
“…Psychoactive tryptamines, particularly psilocybin and psilocin, have recently garnered a great deal of interest because of their potential to treat disorders including anxiety, addiction, and depression (Johnson & Griffiths, 2017;Carhart-Harris & Goodwin, 2017). Of note, psilocybin was recently granted the 'breakthrough therapy' designation by the US Food and Drug Administration (Feltman, 2019).…”
Section: Chemical Contextmentioning
confidence: 99%
“…A wide variety of naturally occurring organisms, including over 200 species of 'magic' mushrooms, contain psychoactive tryptamine compounds (Stamets, 1996). Of these compounds, psilocybin has received the most scientific and commercial attention because of recent studies demonstrating its potential for treating mood disorders including addiction, anxiety, depression and PTSD (Johnson & Griffiths, 2017;Carhart-Harris & Goodwin, 2017).…”
Section: Chemical Contextmentioning
confidence: 99%
“…Renewed interest in 1 as a prodrug of therapeutic agent 2 was accompanied by studies on its relative physiological and psychological safety in controlled and well‐defined settings . Studies showed promising outcomes in the therapy of cancer‐related psychiatric distress and anxiety, treatment‐resistant depression, and substance addiction . However, a commonly acknowledged drawback of these studies is the low number of participants due to administrative barriers .…”
Section: Concluding Remarks: Psilocybin As a Future Therapeuticmentioning
confidence: 99%
“…[25] Studies showedp romising outcomesi nt he therapy of cancer-related psychiatric distress and anxiety, treatment-resistant depression, and substancea ddiction. [26] However,acommonlya cknowledged drawback of these studies is the low number of participants due to administrative barriers. [27] With the aim for the FDA to register 1 as am edication for psychological distress, phase III studies are currently being planned.…”
Section: Concluding Remarks:psilocybin As Af Uture Therapeuticmentioning
confidence: 99%